FURNITURE DESIGN ANALYSIS OF CULINARY INDUSTRY OUTLETS IN BANDUNG CITY - Hadi, Nefi Salsabila; Joedawinata, Ahadiat (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
Furniture design is a facility that has an important role for an outlet. In addition to providing functions as needed, furniture design can also add an aesthetic role and strengthen the identity of the selling product in this context, namely Mixue Ice Cream & Tea products. This research aims to analyze the type of furniture design used in Mixue Ice Cream & Tea outlets in Bandung City. By using descriptive research methods, then researchers conducted direct observations of furniture facilities at Mixue outlets in the city of Bandung, and analyzed the types of furniture designs found at these outlets. The results showed the diversity of the types of furniture designs used at Mixue Ice Cream & Tea outlets in the city of Bandung. This research can be a consideration and reference for outlet owners, especially the culinary industry and also for interior designers, to pay more attention to the types of furniture used to suit the needs of activities and facilities in designing a culinary industry outlet, in order to improve customer experience and operational effectiveness of an outlet.